Alinéa suicide postvention program: a codesigned early proactive intervention for survivors - Coquelin, Mélanie; Kopp-Bigault, Céline; Barinoil, Canelle; Berrouiguet, Sofian; Guarnaccia, Cinzia (Frontiers in Psychology, 2024)
Background: Bereavement following suicide is a risk factor for major depression, posttraumatic stress disorder, suicidal behavior, the emergence of bipolar disorders and prolonged mourning. The scientific literature agrees on the need to deploy support services tailored to the specificities of post-suicide bereavement. Alinéa responds to these specificities with an early and proactive individual postvention program.Method: This article presents the process of co-designing Alinéa by involving participants who have been exposed to suicide either through the loss of a loved one or in the course of their work. This co-design led to the creation of a collaborative system for early, proactive professional intervention. The Alinéa program, design intervention objectives and protocol, are